Assessment of Anti-Hypertensive Drug Adherence by Serial Aldosterone-To-Renin Ratio Measurement - Buffolo, Fabrizio; Sconfienza, Elisa; Burrello, Jacopo; Losano, Isabel; Mengozzi, Giulio; Priolo, Gabriella; Avataneo, Valeria; D’Avolio, Antonio; Veglio, Franco; Rabbia, Franco; Mulatero, Paolo; Monticone, Silvia (Frontiers in Pharmacology, 2021)
Reduced or absent compliance to anti-hypertensive treatment is a major obstacle to the achievement of blood pressure target in patients with arterial hypertension. Current available methods for therapeutic adherence assessment display low accuracy, limited applicability in clinical practice and/or high costs. We designed a prospective study to evaluate the accuracy of serial measurement of aldosterone-to-renin ratio (ARR) to assess the therapeutic compliance to renin-angiotensin-aldosterone system (RAAS) inhibitors. We prospectively enrolled 80 subjects: 40 patients with arterial hypertension and 40 normotensive controls. The ARR was evaluated at baseline and 2 and 8 weeks after initiation of a RAAS inhibitor in patients with hypertension, and at baseline and 2 weeks for the control group. Adherence to the prescribed therapy was confirmed by therapeutic drug monitoring. We observed a significant increase of renin levels and reduction of aldosterone levels after RAAS inhibitors initiation, with consequent reduction of ARR. Delta ARR (ΔARR), defined as relative change in ARR before and after treatment initiation, provided high accuracy for determination of therapeutic compliance, with an area under the curve (AUC) of 0.900 at 2 weeks and 0.886 at 8 weeks. A cut-off of -48% of ΔARR provided 90% sensitivity and 75% specificity, at 2 and 8 weeks. In conclusion, the measurement of ΔARR is a powerful test, cheap and widely available to accurately identify the non-adherence to RAAS inhibitors treatment. Herein we propose the implementation of ΔARR in clinical practice through a multi-step flow-chart for the management of patients with uncontrolled blood pressure, with identification of those suspected of non-adherence, reserving therapeutic drug monitoring for non-adherence confirmation.